Supporting nursing students from diverse cultural backgrounds. (August 2020) - Wiredu, Immanuel; Roberts, Debbie
Highlights: Culturally and linguistically diverse individuals co-exist in clinical practice. Cultural issues impact on the learner mentor relationship. Both parties should understand the consequences for learning.